Pembuktian Ilmiah VS Alibi: Bagaimana Ilmu Forensik Mengatasi Tantangan Pembelaan pada Kasus Raden Adante - Adiatma Nugroho; Handar Subhandi Bakhtiar (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2024)
Scientific evidence has become an important element in modern criminal justice, especially in complex cases such as Raden Adante, where alibis are used as the main defense strategy to undermine forensic evidence. In this case, scientific methods such as DNA analysis, digital traces, and toxicology examination succeeded in breaking the defendant's alibi. This research examines how scientific evidence can overcome the challenges of alibi strategies which are often used to confuse the investigative process. This study shows that accurate and standardized forensic evidence is able to objectively confirm the presence of the defendant at the scene of the crime, thereby strengthening fair and effective law enforcement efforts. The research uses a juridical-normative approach with qualitative analysis, examining regulations, legal doctrine, and expert views to assess the role of scientific evidence in dealing with alibi defenses.